Analysis of microbial composition in different dry skin areas of Beijing women - Wang, Jingtao; Li, Benyue; Zhang, Yuanman; Ma, Wei; Jia, Ting; Yang, Jie; Zhang, Yexiang; Qi, Fengwei; Jia, Yan; Song, Liya (Frontiers in Microbiology, 2025)
IntroductionThe composition of the skin microbiota is shaped by the interaction of multiple factors, with area-specific changes and physiological characteristics in the skin having the most profound impact. The back of the hand and lower leg are two dry areas of human skin. Whether their microbial compositions are consistent, as well as the changes in skin microbiota at these two areas among individuals with dry skin, warrant further discussion.MethodsUsing 16S rRNA sequencing, we analyzed the differences of microbiota in dry skin areas of 54 young women and their changes in dry populations. Concurrently, key physiological parameters (Hydration, TEWL, sebum secretion) were measured.ResultsAnalysis of physiological parameters showed that Hydration, TEWL and sebum secretion were significantly lower (P < 0.05) in the lower leg compared to the back of the hand. Hydration was significantly lower (P < 0.05) at the same skin area in the dry-skinned population compared to the healthy population. Regarding microbial composition, the relative abundance of Firmicutes and Proteobacteria was significantly higher on the lower leg compared to the back of the hand, whereas the relative abundance of Actinobacteriota was notably greater on the back of the hand than on the lower leg (P < 0.05). Compared to the lower leg, the back of the hand showed a higher relative abundance of Cutibacterium (34.19% vs. 8.68%), whereas the lower leg was predominantly colonized by Streptococcus (17% vs. 13.76%). At the genus level, the relative abundance of Streptococcus was significantly increased in the dry skin group, whereas a decreasing trend was observed for Cutibacterium. Redundancy analysis (RDA) showed that Streptococcus was negatively correlated with Hydration, TEWL, and sebum, and vice versa for Cutibacterium.DicussionThese findings suggest that differences in skin microbiota are primarily influenced by a combination of skin area micro environmental factors and not solely dependent on dryness status, suggesting that area-specific ecological niche design should be taken into account when conducting clinical interventions.